Efektivitas Penggunaan Eceng Gondok (Eichornoa crassipes) Dan Ijuk Sebagai Substrat Untuk Meningkatkan Daya Tetas Telur Ikan Cupang (Betta splendes) - Humaira, Intan; Nurfadillah, Nurfadillah; Ismarica, Ismarica (Jurnal Kelautan dan Perikanan Indonesia, 2024)
Betta fish is a freshwater fish originating from several countries in Southeast Asia, including Indonesia, Thailand, Malaysia, Brunei Darussalam, Singapore and Vietnam. Betta fish is a popular ornamental fish because of its unique size and attractive color, making betta fish a promising cultivation prospect. However, betta fish cultivation still has several problems, namely the low egg hatching rate. Factors that affect the low egg hatching rate include the use of substrates. This study aims to determine the effectiveness of using water hyacinth and palm fiber as a substrate to increase egg hatchability and survival of betta fish. The method used in this study was a completely randomized design (CRD) using 4 treatments (A: control, B: 100% water hyacinth substrate, C: 100% palm fiber substrate, D: 50% water hyacinth and palm fiber substrate combination. 50%) and 3 repetitions. The results obtained from this study were based on the results of analysis of variance (ANOVA), namely the use of water hyacinth and palm fiber as substrates had a significant effect (p0.05) on hatching rate and survival. The conclusion from the results of the study was that treatment B (water hyacinth 100%) showed the best results in HR parameters (95.80 1.37%) and survival (95.63 1.48%).